FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS KONSUMEN DI UD. MEKAR JAYA BUAH KOTA TANGERANG: (Studi Kasus Kepuasan Konsumen di UD. Mekar Jaya Buah) - Ahmad Nursodik; Aep Saefullah; Usman Ali; Sonia Destiana; Putri Lolyta; Ramadani Pardian; Patria Adiguna (Jurnal Multidisiplin Indonesia, 2023)
This study aims to identify factors that influence customer satisfaction and loyalty at UD. Mekar Jaya Buah, a fruit trading company in Tangerang City. As business competition is getting tougher, a deep understanding of customer satisfaction and loyalty is essential to develop effective marketing strategies. This research uses a descriptive qualitative approach which was conducted for two months, from June to July 2023. Data collection techniques through interviews, observation, and literature. The results revealed that product quality and customer service are the main factors that influence consumer satisfaction and loyalty. Consumers value high-quality products and positive interactions with service staff. Prices that match the value of the product also contribute to consumer satisfaction. Other factors include ease of access, shopping convenience, and feelings of attachment to the brand. The implication of this research is the need for UD. Mekar Jaya Buah to continuously improve the quality of products and services, and consider the right pricing strategy. A better understanding of consumer preferences and expectations will help companies design more careful marketing strategies. In addition, this research also contributes to further understanding of the dynamics of consumer behavior in the context of the fruit trading industry.